El canto de la sibila: II. Calaluña y Baleares - Muntané, Maricarmen Gomez (Madrid Editorial Alpuerto, 1997)
CONTENIDO: Agradecimientos Introducción Notas críticas Bibliografía Discografía Edición: I- Iudici signum II- Iudici signum III- Iudici signum IV- Iudici signum V- Iudici signum VI- Iudici signum VII- Al jorn del judici VIII- Al jorn del judici IX- Al jorn del judici X- Al jorn del judici XI- Iudici signum. Al jorn del judici XII- Iudici signum (Anónimo) XIII- Al jorn del judici (Bartolomé Cárceres) XIV- Al jorn del judici (Alonso) XV- Lo jorn del judici XVI- Al jorn del judici XVII- La Sibila (B. Torres) XVIII- Antiguo canto de la Sibila (Felipe Pedrell)
The Song of the Sibyl is a liturgical drama and a Gregorian chant, the lyrics of which comprise a prophecy describing the Apocalypse, which has been performed in churches on Majorca (Balearic Islands, Spain) and Alghero (Sardinia, Italy), and some Catalan churches, in the Catalan language on Christmas Eve nearly uninterruptedly since medieval times. It was declared a Masterpiece of the Oral and Intangible Heritage of Humanity by UNESCO on 16 November 2010.
Keywords: Middle Ages (500-1400); 20th Century (1901-2000); Vocal music; Music history; The Song of the Sibyl; Plainchant; Liturgy; Catholicism; Church music; Play (theater); Catalonia (Spain); Balearic Islands